Telehealth in emergency medicine: A consensus conference to map the intersection of telehealth and emergency medicine. (21st July 2021) - Hayden, Emily M.; Davis, Christopher; Clark, Sunday; Joshi, Aditi U.; Krupinski, Elizabeth A.; Naik, Neel; Ward, Michael J.; Zachrison, Kori S.; Olsen, Erica; Chang, Bernard P.; Burner, Elizabeth; Yadav, Kabir; et al.
Abstract: Introduction: Telehealth has the potential to significantly change the specialty of emergency medicine (EM) and has rapidly expanded in EM during the COVID pandemic; however, it is unclear how EM should intersect with telehealth. The field lacks a unified research agenda with priorities for scientific questions on telehealth in EM. Methods: Through the 2020 Society for Academic Emergency Medicine's annual consensus conference, experts in EM and telehealth created a research agenda for the topic. The multiyear process used a modified Delphi technique to develop research questions related to telehealth in EM. Research questions were excluded from the final research agenda if they did not meet a threshold of at least 80% of votes indicating "important" or "very important." Results: Round 1 of voting included 94 research questions, expanded to 103 questions in round 2 and refined to 36 questions for the final vote. Consensus occurred with a final set of 24 important research questions spanning five breakout group topics. Each breakout group domain was represented in the final set of questions. Examples of the questions include: "Among underserved populations, what are mechanisms by which disparities in emergency care delivery may be exacerbated or ameliorated by telehealth" (health care access) and "In what situations should the quality and safety of telehealth be compared to in‐person care and in what situations should it be compared to no care" (quality and safety). Conclusion: The primary finding from the process was the breadth of gaps in the evidence for telehealth in EM and telehealth in general. Our consensus process identified priority research questions for the use of and evaluation of telehealth in EM to fill the current knowledge gaps. Support should be provided to answer the research questions to guide the evidenced‐based development of telehealth in EM.